The Role of Islamic Education in Overcoming the Social-Ecological Crisis in the Modern Era - Nisa, Ainun; Annisa, Aulia; Zulhanan, Zulhanan; Murtadho, Ali; Baharuddin, Baharuddin (STIT Ahlussunnah Bukittinggi, 2025)
The socio-ecological crisis in the modern era has become a global challenge that threatens the sustainability of human life, ranging from environmental damage, ecological poverty, to social inequality as a result of uncontrolled exploitation of natural resources. This study aims to analyze the role of Islamic Education in providing strategic solutions to overcome this crisis through strengthening spiritual values, ecological ethics, and sustainability character. The research uses a qualitative method with a content analysis approach to classical Islamic literature, contemporary research results, and national education policies related to the environment. The results show that Islamic education has significant potential in building ecological awareness based on tauhid, amanah, and rahmatan lil 'alamin, integrating eco-theological values into the curriculum, and encouraging action-oriented educational practices through the habit of environmentally friendly behavior. The implications of the research emphasize the need to reorient the Islamic Religious Education curriculum, strengthen ecological pedagogy, and foster collaboration among educational institutions to create a generation of Muslims who play an active role in mitigating the socio-ecological crisis in a sustainable manner.